Examining the Relationship Between Economic Abuse and Mental Health Among Latina Intimate Partner Violence Survivors in the United States. Issue 1 (January 2021) - Davila, America L.; Johnson, Laura; Postmus, Judy L.
Currently, Latinos constitute the second largest and fastest growing minority group in the United States. Among this population, one in every six Latinas experience intimate partner violence (IPV) in her lifetime. Research has documented significant detrimental effects of physical, sexual, emotional, and psychological IPV on the physical, emotional, and cognitive well-being of various cultural/ethnic groups; however, few studies have focused on economic abuse, which may include tactics of economic control, economic exploitation, and employment sabotage. Research examining economic abuse against racial/ethnic minorities, particularly Latinos, is needed. To address these gaps, baseline data from a larger treatment outcome study were used to examine the associations between economic abuse and the mental health symptoms reported by 245 Latina IPV survivors in the United States. When examining the economic abuse experiences reported by Latinas in this sample, the results indicated that the most commonly reported form of economic abuse was economic control (e.g., restricting access to money and financial information). Multiple regression analyses revealed that economic abuse did not uniquely predict mental health after accounting for other forms of IPV victimization and sociodemographic characteristics. Limitations of this study are discussed, and directions for future research designed to enhance our understanding of economic abuse against various racial/ethnic groups (such as Latinas) are presented.